Isolation of root-associated Pseudomonas and Burkholderia spp. with biocontrol and plant growth-promoting traits. Issue 1 (2nd January 2017) - Wakelin, Steve; Young, Sandra; Gerard, Emily; Mander, Carolyn; O'Callaghan, Maureen
ABSTRACT: Novel, root-associated Pseudomonas and Burkholderia strains with biological control and plant growth-promoting (PGP) traits are being sought for biotechnological application in agriculture. We present a new isolation approach for recovery of rhizoplane and/or endophytic Pseudomonas and Burkholderia spp. with desirable biocontrol and PGP phenotypes. The method may enable better targeted biodiscovery of these two important genera.